Vaccination with dendritic cells pulsed with hepatitis C pseudo particles induces specific immune responses in mice - Weigand, Kilian; Voigt, Franziska; Encke, Jens; Hoyler, Birgit; Stremmel, Wolfgang; Eisenbach, Christoph (World journal of gastroenterology, 2012)
Vaccination with dendritic cells pulsed with hepatitis C pseudo particles induces specific immune responses in mice